Drawing Insects and Phenomenology - Fauzi Naeim (Wacana Seni Journal of Arts Discourse, 2017)
he article is formed from a dialogue between my drawings of insects and phenomenological writings such as those from Martin Heidegger, Hans-Georg Gadamer and Maurice Merleau-Ponty. Phenomenology is a scheme that privileges the experience in perceiving an object as it presents itself to our consciousness. According to Martin Heidegger in Being and Time, "phenomenology means to let that which shows itself be seen from itself in the very way in which it shows itself from itself" (1962: 58). The drawings selected here are of insects, which made up a special repertoire in my series of sketchbooks. The drawings were done using pen, ink, and watercolour on paper. Here, I establish my personal perspectives on what draws me to the studies in the first place—of my attraction to insects; lines, shape, texture and colour—while viewing artistic process in the richness of phenomenology. I end my article with a note on Heidegger's argument that art is man's saving grace from technological enframing.